2021
DOI: 10.1096/fj.202100061rr
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GCN2 in macrophages promotes white adipose tissue browning and lipolysis under leucine deprivation

Abstract: We have previously shown that leucine deprivation stimulates browning and lipolysis in white adipose tissue (WAT), which helps to treat obesity. Adipose tissue macrophages (ATMs) significantly influence WAT browning and lipolysis. However, it is unclear whether ATMs are involved in leucine deprivation-induced browning and lipolysis in WAT; the associated signals remain to be elucidated. Here, we investigated the role of ATMs and the possible mechanisms involved in WAT browning and lipolysis under leucine-depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Recent studies have shown that the activation of GCN2 signaling in amygdalar protein kinase C (PKC)-δ neurons and macrophages promote WAT browning under Leu deprivation [ 40 , 63 ]. Researchers have found that Leu deficiency-induced WAT browning could be blocked by GCN2 deletion in amygdalar PKC-δ neurons, which is reversed by the over-expression of amino acid-responsive gene activating transcription factor 4 (ATF4) and is mediated by amygdalar PKC-δ neurons activity and the SNS [ 40 ].…”
Section: The Effects Of Essential Amino Acid Deprivation or Restricti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the activation of GCN2 signaling in amygdalar protein kinase C (PKC)-δ neurons and macrophages promote WAT browning under Leu deprivation [ 40 , 63 ]. Researchers have found that Leu deficiency-induced WAT browning could be blocked by GCN2 deletion in amygdalar PKC-δ neurons, which is reversed by the over-expression of amino acid-responsive gene activating transcription factor 4 (ATF4) and is mediated by amygdalar PKC-δ neurons activity and the SNS [ 40 ].…”
Section: The Effects Of Essential Amino Acid Deprivation or Restricti...mentioning
confidence: 99%
“…Further analyses revealed that GCN2 activation in macrophages reduces the expression of monoamine oxidase A (MAOA), resulting in increased NE secretion from macrophages to adipocytes, and an enhanced WAT browning. In addition, GCN2 signaling in ATMs similarly mediates Leu deficiency-increased WAT lipolysis [ 63 ].…”
Section: The Effects Of Essential Amino Acid Deprivation or Restricti...mentioning
confidence: 99%
“…Male C57BL/6J wild-type (WT) mice were purchased from the Shanghai Laboratory Animal Co. Ltd (SLAC; Shanghai, China). Gcn2 -floxed mice 56 were intercrossed with Villin -cre mice 48 (Shanghai Biomodel Organism Science & Technology Development Co.,Ltd., Shanghai, China) to generate the IEC-specific Gcn2 IKO mice. All mice were housed in laboratory cages at a temperature of 23 ± 3 °C and humidity of 35 ± 5%, under a 12/12 h dark/light cycle, with free access to a regular chow diet (SLAC) and water.…”
Section: Methodsmentioning
confidence: 99%
“…Male C57BL/6J wild-type (WT) mice were purchased from the Shanghai Laboratory Animal Co. Ltd (SLAC; Shanghai, China). Gcn2oxed mice 42 were intercrossed with Villin-cre mice (Shanghai Biomodel Organism Science & Technology Development Co.,Ltd., Shanghai, China) to generate the IECspeci c Gcn2 IKO mice. All mice were housed in laboratory cages at a temperature of 23 ± 3°C and humidity of 35 ± 5%, under a 12/12 h dark/light cycle, with free access to a regular chow diet (SLAC) and water.…”
Section: Mice Tissue Preparation and Iec Isolationmentioning
confidence: 99%